PENGARUH TEKANAN PERAN DALAM PEKERJAAN DAN KOMITMEN ORGANISASI TERHADAP KEINGINAN UNTUK BERPINDAH TEMPAT KERJA (Studi Empiris pada Auditor KAP di Kota Malang) - Weldy, Gustaf Eza (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study was conducted to determine the effect of role ambiguity, role conflict, role overload, and organizational commitment to the turnover intentions of auditors who worked on Public Accountant Firm (KAP) in Malang. In this explanatory study, researchers used a quantitative approach to look at the effects of role stress that consist of role ambiguity, role conflict and role overload, and organizational commitment to the turnover intentions for auditors who worked on KAP in Malang. Researchers build initial hypothesis that there is a positive influence between the role stress against the turnover intentions and there is a negative influence on the organizational commitment to the turnover intentions for auditors. Statistical calculation by using the t test to obtain the result that all the independent variables affect the desire to move the workplace. Role Ambiguity variables have most significant influence on the turnover intentions for auditors. The hypothesis proposed at the beginning of the study can be accepted, except the second hypothesis. Corrections and improvements such as the socialization of the duties and responsibilities of each personal at the start when entering the work environment is expected to reduce role stress. Keywords: Role Stress, Organizational Commitment, Turnover Intentions